Characteristics of a digital literary translation publisher: revisiting Bourdieu's mapping of the publishing field. (2nd January 2019) - Marin-Lacarta, Maialen
ABSTRACT: Bourdieu defined the French publishing field after conducting a study of 61 publishers in 1999. His study identified key features that can help us define the position of a publisher in the field. How has the field changed since then? Are these features useful in defining other publishers? Are there any features specific to digital publishers? This article revisits Bourdieu's study and tests his observations about the polarised publishing field through a case study of a Barcelona-based publishing initiative that issues literary translations in e-book format. The data collection for this study followed an ethnography-inspired approach, involving participant observation, field notes, reflective diaries, semi-structured interviews, and the collection of translation drafts, correspondence and paratexts. Book reviews and blog posts were also collected to study the dissemination of the translations. The results showed that many of Bourdieu's observations remain relevant, and the characteristics he defined are useful for understanding many of the changes that have taken place in the last two decades. New categories were created to describe specific features of our case study and to show how digital advances have created possibilities for new forms of publishing.